2013
DOI: 10.1063/1.4826900
|View full text |Cite
|
Sign up to set email alerts
|

Electrochemical synthesis of large diameter monocrystalline nickel nanowires in porous alumina membranes

Abstract: In this work, the synthesis of long, single-crystal nickel nanowires (NWs) using dc electrodeposition is reported. Porous alumina membranes with 220 nm mean pore diameter were used as a template. This diameter is much larger than what is usually reported in single crystal NWs synthesis. The dependence of the NW crystal structure upon applied voltage as well as the change in crystal structure along the NW's length is also investigated. Finally, in order to get sufficient understanding of the present results, a … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
17
0

Year Published

2014
2014
2023
2023

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 21 publications
(18 citation statements)
references
References 29 publications
1
17
0
Order By: Relevance
“…38 However the preferred orientation depends on the deposition conditions. 33 In the case of the electrodeposition technique it has been reported that the crystallinity depends on electrodeposition parameter like deposition potential and temperature. 33 By controlling the temperature and potential, single crystal of Ni nanowires has been produced.…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…38 However the preferred orientation depends on the deposition conditions. 33 In the case of the electrodeposition technique it has been reported that the crystallinity depends on electrodeposition parameter like deposition potential and temperature. 33 By controlling the temperature and potential, single crystal of Ni nanowires has been produced.…”
Section: Resultsmentioning
confidence: 99%
“…33 In the case of the electrodeposition technique it has been reported that the crystallinity depends on electrodeposition parameter like deposition potential and temperature. 33 By controlling the temperature and potential, single crystal of Ni nanowires has been produced. 33 It has been also reported that the electrodepostion method can allow accomplishing the uniform preferred growth orientation by varying the applied potential.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Furthermore, tuning of their magnetic properties can be done by adjusting electrodeposition conditions, such as bath temperature, 8 deposition potential, [9][10][11] electrolyte composition and pH value. 12 There are several strategies to modify the NW arrays in order to produce materials that differ from the parallel array of homogeneous nanowires.…”
Section: Introductionmentioning
confidence: 99%
“…Although the preparation of Ni nanowire arrays by using template-assisted electrochemical deposition method has been extensively studied [25][26][27][28][29][30][31], the control of growth orientation and understanding the mechanism are challenged. In this work, we prepared Ni nanowire arrays by using an AAO template-assisted electrodeposition method.…”
Section: Introductionmentioning
confidence: 99%